Beyond glycemic control: the cardiac and hepatic benefits of SGLT2 and DPP-4 inhibitors in mitigating chronic cadmium-induced inflammation, oxidative/nitrative stress, apoptosis and fibrosis - Hassan, Fatma E.; Hassanien, MennaAllah M.; Selmy, Asmaa; Mahmoud, Lamiaa Mohamed; Darwish, Amal; Aldreny, Basant A. (Frontiers in Physiology, 2026)
BackgroundCadmium (Cd) is a hazardous ecological contaminant implicated in substantial oxidative stress (OS), nitrative stress, inflammation, apoptosis and fibrosis, particularly in the heart and liver.ObjectiveThis study aims to contrast the protective effects of “Canagliflozin; Cana” versus “Sitagliptin; Sita” in countering the chronic Cd-induced cardiac and hepatic damage.MethodsFour groups of adult male Wistar rats (6 each) were created: Control, Cd-exposed; rats received 100 mg/L CdCl2 via drinking water, Cd + Cana; rats received Cana 10 mg/kg, orally in parallel with CdCl2 (100 mg/L), and Cd + Sita; rats received Sita 10 mg/kg, orally concomitant with CdCl2 (100 mg/L). Following a 12-week course of treatment of all regimens, serum glucose, albumin, aspartate transaminase, alanine transaminase, lactate dehydrogenase, creatine Kinase-MB (CK-MB), Troponin I and Troponin C (cTnC) were measured. Cardiac and hepatic tissues were subjected to quantitative real-time polymerase chain reaction assays for Notch1, transforming growth factor-β, SMAD3, alpha-smooth muscle actin (α-SMA), and SMAD7 expression levels. In addition, interleukin-10/-1β, tumor necrosis factor-α, reduced glutathione, and malondialdehyde were evaluated. Besides, there was a cardiac and hepatic histological evaluation after hematoxylin and eosin, and Masson staining, as well as immunohistochemistry measurement of caspase 3, nuclear factor kappa B (NF-κB) and inducible nitric oxide synthase (iNOS). Results were analyzed using one-way ANOVA followed by Tukey’s post hoc and then represented as mean ± standard deviation. Differences among groups were considered statistically significant when p value is ≤0.05.ResultsThere were no substantial changes in blood glucose levels across all groups, which confirmed the model’s normoglycemic nature. Therefore, independent from their glycemic effect, both Cana and Sita significantly but comparably (p > 0.05) improved cardiac and hepatic OS, inflammation, apoptosis, and fibrosis associated with chronic Cd exposure. However, Cana demonstrated greater improvement (p < 0.05) in serum CK-MB and cTnC, cardiac (α-SMA) and hepatic (collagen area%) fibrosis, cardiac and hepatic apoptosis (caspase 3%), inflammation (NF-κB%) and nitrative stress (iNOS%) and restored their architecture.ConclusionBoth medications showed comparable cardio-hepatic protective effects. Yet, Cana outperformed Sita as a potentially effective therapy to counteract the negative consequences of chronic Cd-induced cardiac and hepatic pathologies.